2013
DOI: 10.1134/s0021364013190041
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the coercive field in ferroelectrics at the nanoscale

Abstract: Gaynutdinov, R. V.; Minnekaev, M.; Mitko, S.; Tolstikhina, A. L.; Zenkevich, A.; Ducharme, Stephen; and Fridkin, Vladimir M., "Scaling of the Coercive Field in Ferroelectrics at the Nanoscale" (2013). Stephen Ducharme Publications. 91.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…It is worth noting that the obtained values of E pv for both thicknesses of BaTiO 3 are less than the corresponding coercive field E c . It is because, unlike bulk crystals, the previously obtained values of E c for ultrathin BaTiO 3 films [30,31] are very close to the intrinsic Landau-Ginzburg value E c ∼ 10 6 V/cm for BaTiO 3 [31].…”
supporting
confidence: 60%
“…It is worth noting that the obtained values of E pv for both thicknesses of BaTiO 3 are less than the corresponding coercive field E c . It is because, unlike bulk crystals, the previously obtained values of E c for ultrathin BaTiO 3 films [30,31] are very close to the intrinsic Landau-Ginzburg value E c ∼ 10 6 V/cm for BaTiO 3 [31].…”
supporting
confidence: 60%
“…Here, for the first time, a scaling behavior of the same type is reported for nanoscale barium titanate films grown by laser epitaxy [38].Measurements were performed on aPt-BaTiO 3 -Au capacitor using PAM (see Figure 4). Electrodes were formed on a barium titanate surface by lithography and were circular with a radius of a few micrometers.…”
Section: Coercive Field Scalingmentioning
confidence: 56%
“…The experiments concluded that in BaTiO 3 films of 20-nm thickness, the coercive field is around 70 KV mm −1 [42]. Hence, for the ideal crystal, in order to recognize the physical phenomena clearly it is essential to apply a very high external field in the simulation for the sample with size 25.2 nm 2 .…”
Section: B Electrocaloric Effect Of Batiomentioning
confidence: 98%
“…Hence, when the domain-wall energy is sufficiently small (S J = 1), an antiferroelectric-type hysteresis is visible. According to the measurements by Gaynutdinov et al [42], the coercive field is around 70 KV mm −1 for BaTiO 3 thin films with a thickness of 20 nm. The simulated sample size is 25.2 nm 2 in this work, and for S J = 2 the coercive field is about 120 KV mm −1 , which is in good agreement to the experimental value.…”
mentioning
confidence: 95%